KORELASI GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOUR (OCB) - Undarwati, Anna (Jurusan Psikologi, Fakultas Ilmu Pendidikan, Universitas Negeri Semarang, 2009)
The research focused on finding correlation between transformational leadership style and organizational citizenship behaviour (OCB). The subject were 100 employees of PD. Pasar Surya Surabaya. Data was collected by MLQ (Multifactor Leadership Questioner) and organizational citizenship behaviour (OCB) scale. Hypothesis is tested by product moment correlation technique. The result shown that there was a significant correlation between transformational leadership style and organizational citizenship behaviour (OCB) with rxy = 0,504, p < 0,001. TransformationaI leadership style has influencing 25,5% for organizational citizenship behaviour (OCB). It means that 75% was influenced by others.